Town Center Strategic Plan - Emon, Ayeshah (My University, 2009)
Between March and July of 2009, the Strategic Planning Design Team developed a mission and vision, articulated guiding principles, set operating criteria and proposed a governance model for the Town Center. The team outlined a model for starting up operations and staffing and began a process for budget development and business planning. The following narrative provides a summary of planning and priorities.